Good Policy a Prerequisite for Good Agriculture - Inter-American Institute for Cooperation on Agriculture (Inter-American Institute for Cooperation on Agriculture, 2005)
The In a Nut shell series is designed to stimulate interest and inform on issues .. of importance to sustainable agricultural development in Caribbean countries